THE COURTESY CALL: STUDY ON POLITENESS OF FICTION CHARACTERS - I Dewa Putu Wijana (Sanata Dharma University, 2020)
This research is an attempt to study politeness issues based on utturances of Osamu Dazais short story characters entitled The courtesy Call, the English translation from Japanese Shinyu Kokan by Ivan Morris. By using politeness maxim theory proposed by Leech, it is found that the antagonist often violates 6 politeness maxims which are tend to obey by the protagonist and his wife. The violation and the obedience of politeness maxims constitute a reflection of character differences intended by the writer. Utterances expressed by Fictions characters are a rich source to exploit for studying politeness for pragmatic studies as their creation are based on careful observations of the author toward the world realities.